The individual and combined effects of social networks and loneliness on life satisfaction among community-dwelling residing older adults: a longitudinal study - Foong, Hui Foh; Ibrahim, Rahimah; Hamid, Tengku Aizan; Bagat, Mohamad Fazdillah (Multidisciplinary Digital Publishing Institute, 2023)
Social networks and loneliness are correlates of life satisfaction in old age. However, the evidence of the combined effects of social isolation and loneliness on life satisfaction is lacking; therefore, this study also aimed to investigate the combined effects of social networks and loneliness on life satisfaction in Malaysian older adults. Data from two waves of the “Neuroprotective Model for Healthy Longevity among Malaysian Older Adults” study were extracted. The first wave of data collection was completed in February 2013, while the second wave was conducted three years after the first wave. The main statistical analysis used was multivariable logistic regression. For individual effect, social networks (B = 0.375, p = 0.007), but not loneliness (B = −0.178, p = 0.368) significantly determined life satisfaction. Increasing social network size causes increasing life satisfaction. For combined effects, those in “the lone farmers” group (B = 0.279, p = 0.044) and “the majority” group (B = −0.413, p = 0.004) were linked to life satisfaction. Social engagement in older people is important for wellbeing in later life. Therefore, community programs and investing in a quality relationship should be encouraged to obtain adequate support and ultimately promote higher life satisfaction.